Physiotherapy intervention in the management of rheumatoid arthritis patients: A systematic review (2017)
Objective To evaluate and critical review the available scientific evidence and determine the physical therapy treatment for patients with rheumatoid arthritis (RA) Search strategy Systematic searches were conducted for randomized clinical trials (RCTs) published between 2000 and 2015 in the following databases: PubMed, ScienceDirect and Cochrane Library. Following the evaluation of methodological quality with two scales PEDro and SIGN. RCTs should include physiotherapy intervention (physical exercise, physical agents, tele-rehabilitation or alternative techniques), be applied in patients with RA and that measured the following variables: pain, stiffness, function and/or quality of life. Study selection 28 RCTs were included; 21 correspond to interventions with therapeutic exercise, 5 with physical agents, 1 to alternative techniques and 1 tele-rehabilitation. Synthesis of results Evidence shows that therapeutic exercise has a significant impact on functional capacity, especially in hand function, mobility and displacement. Physical agents showed no statistical difference between the groups, but does at the beginning and end of the intervention. The Taichi as an alternative and complementary to traditional intervention technique improves physical and mental condition. Finally, physical activity based on Internet with one supervision, exercise equipment and support is effective as an intervention strategy. Conclusions Based on the results of this review can be established that since there are different physical therapy interventions for patients with RA, within which the most widely used and with greater positive effects is the therapeutic exercise. © 2016 Asociación Española de Fisioterapeutas